The Impact of Digital Transformation on the Future Jobs: Perspectives from Experts in Libyan Telecommunications Companies - Hasan Emran; Milad Salem; Fathia Elhony (Journal of Business, Management, and Social Studies, 2025)
This study aimed to identify the impact of digital transformation on the future of jobs by exploring its effects on the labor market and future occupations. Data were collected from a group of experts working in Libyan telecommunications companies, totaling 59 participants. A descriptive analytical approach was employed to analyze and interpret the data. The results revealed that digital transformation has a significant impact on the future of jobs and the quality of skills required, leading to changes in the nature of jobs and their skill requirements. The level of optimism regarding digital opportunities was high (88.1%). However, the findings also indicated that some jobs are expected to disappear (91.5%). Artificial intelligence (84.7%) was identified as the most critical future job field, followed by cybersecurity (64.4%) as one of the most in-demand job areas. The study’s novelty lies in providing rare empirical data on digital transformation within the Libyan telecommunications sector, specifically capturing the unique tension between high expert optimism and the projected disappearance of traditional roles. It moves beyond global trends to identify AI and cybersecurity as the localized priority shifts for the Libyan labor market.